2016
DOI: 10.1055/s-0042-108590
|View full text |Cite
|
Sign up to set email alerts
|

Activities and Prevalence of Proteobacteria Members Colonizing Echinacea purpurea Fully Account for Macrophage Activation Exhibited by Extracts of This Botanical

Abstract: Evidence supports the theory that bacterial communities colonizing Echinacea purpurea contribute to the innate immune enhancing activity of this botanical. Previously we reported that only about half of the variation in in vitro monocyte stimulating activity exhibited by E. purpurea extracts could be accounted for by total bacterial load within the plant material. In the current study we test the hypothesis that the type of bacteria, in addition to bacterial load, is necessary to fully account for extract acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 21 publications
3
11
0
Order By: Relevance
“…In our previous studies we reported that the bacterial components lipopolysaccharide (LPS) and Braun-type lipoproteins within extracts of E. purpurea and other botanicals were responsible for essentially all of the in-vitro activation of monocytes/macrophages 1 . Consistent with these findings, our later studies showed that the level of in vitro macrophage activation exhibited by an E. purpurea extract could be predicted by calculating the sum of activities contributed by the prevalence and types of Proteobacteria within the plant material 4 . Furthermore, we found that root and aerial extracts from E. purpurea and E. angustifolia , obtained from six distinctly different regions in North America, exhibited substantial variation in macrophage stimulatory activity (up to 200-fold).…”
Section: Introductionsupporting
confidence: 68%
See 3 more Smart Citations
“…In our previous studies we reported that the bacterial components lipopolysaccharide (LPS) and Braun-type lipoproteins within extracts of E. purpurea and other botanicals were responsible for essentially all of the in-vitro activation of monocytes/macrophages 1 . Consistent with these findings, our later studies showed that the level of in vitro macrophage activation exhibited by an E. purpurea extract could be predicted by calculating the sum of activities contributed by the prevalence and types of Proteobacteria within the plant material 4 . Furthermore, we found that root and aerial extracts from E. purpurea and E. angustifolia , obtained from six distinctly different regions in North America, exhibited substantial variation in macrophage stimulatory activity (up to 200-fold).…”
Section: Introductionsupporting
confidence: 68%
“…Evidence from our lab 14 and others 5,6 supports the theory that the efficacy of E. purpurea against respiratory infections is dependent, at least in part, on its bacterial community (microbiome). Bacterial components of this microbiome can directly impact immune function 15 and plant-endophyte interactions can alter secondary metabolite production of the anti-inflammatory alkylamides 6 .…”
Section: Introductionsupporting
confidence: 67%
See 2 more Smart Citations
“…Recent studies revealed that the immunostimulatory factors in Echinacea and JTT were lipopolysaccharides (LPSs) of plant‐associated Gram‐negative bacteria (Haron et al, ; Kalpana et al, ; Montenegro et al, ; Pugh, Jackson, & Pasco, ; Pugh et al, ; Todd et al, ). These findings opened a possibility that the immunostimulatory activity of other medicinal plants might also arise from LPSs.…”
Section: Introductionmentioning
confidence: 99%